2013
DOI: 10.1021/es3038388
|View full text |Cite
|
Sign up to set email alerts
|

The Biotic Ligand Model Can Successfully Predict the Uptake of a Trivalent Ion by a Unicellular Alga Below pH 6.50 but not Above: Possible Role of Hydroxo-Species

Abstract: In many reported cases, the biotic ligand model (BLM) has been shown to predict the bioavailability of divalent metals toward aquatic biota successfully. However, studies on the bioavailability of nonessential trivalent metals, including aluminum (Al), are relatively scarce. In the present study, short-term scandium (Sc) internalization fluxes (Jint) were measured in Chlamydomonas reinhardtii in order to explore the applicability of the BLM to trivalent metals. Scandium was selected for its chemical similariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 44 publications
8
48
1
Order By: Relevance
“…In the present study, there was a linear relationship between H + activity and Cr 3+ toxicity over the whole pH range, and the values of EC50{CrOH 2+ } ranged from 398 to 1663 nM with the increasing pH from 4.50 to 6.25, indicating that the effect of pH on Cr metal toxicity was a significant competition effect as well as speciation effect between protons and metal ions. This finding was consistent with that reported by Cremazy et al [34], who studied the uptake of a trivalent ion scandium (Sc) by Chlamydomonas reinhardtii , and found H + competitive for binding with Sc 3+ transport sites within the pH range of 4.50 to 6.00, and also suggested that reasonable fit for BLM could also be obtained as a function of the first hydroxo-species ([ScOH 2+ ]) along with proton competition. The results from Table 2 showed that Cr 3+ had a higher affinity to the biotic ligand than CrOH 2+ , which can be correlated to the charge of the ion.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, there was a linear relationship between H + activity and Cr 3+ toxicity over the whole pH range, and the values of EC50{CrOH 2+ } ranged from 398 to 1663 nM with the increasing pH from 4.50 to 6.25, indicating that the effect of pH on Cr metal toxicity was a significant competition effect as well as speciation effect between protons and metal ions. This finding was consistent with that reported by Cremazy et al [34], who studied the uptake of a trivalent ion scandium (Sc) by Chlamydomonas reinhardtii , and found H + competitive for binding with Sc 3+ transport sites within the pH range of 4.50 to 6.00, and also suggested that reasonable fit for BLM could also be obtained as a function of the first hydroxo-species ([ScOH 2+ ]) along with proton competition. The results from Table 2 showed that Cr 3+ had a higher affinity to the biotic ligand than CrOH 2+ , which can be correlated to the charge of the ion.…”
Section: Discussionsupporting
confidence: 91%
“…Besides ionic silver, complexed silver species such as AgCl 2 − (aq) can also act as a labile source of silver ions to bacteria via thermodynamic equilibration between the bulk solution and the cell surface. This observation is consistent with the Biotic Ligand Model [39]. In turn, any uptake by cells will drive a constant and steady flux from nanoparticles, potentially leading to locally elevated concentrations in the vicinity of the nanoparticles [40].…”
Section: Discussionsupporting
confidence: 85%
“…The formation of ternary complexes has been postulated to occur for both divalent metals, including Pb [43,49,50] and Zn, [44,51] and trivalent metals such as Al, [42,52] Sc, [53] Eu [47] and Tm. [45] Indeed, Aristilde et al [44] suggested that the formation of ternary complexes may be universal, irrespective of the specificity of the metal or ligand.…”
Section: Introductionmentioning
confidence: 99%